Assault related injury visits in US emergency departments: An analysis by weekday, month and weekday-by-month. (3rd August 2022) - Khurana, Bharti; Prakash, Jaya; Loder, Randall T.
ABSTRACT: This study investigated the temporal variation (month and day) in assault-related injuries presenting to the US Emergency Departments (ED). An IRB exempt, retrospective review of prospectively collected data was performed using the National Electronic Injury Surveillance System Database from 2005 to 2017 for six categories of assault-related injuries-altercation, sexual assault, robbery, intimate partner violence (IPV), other specified assaults and unknown assault types. National estimates of injuries and associated variables were obtained using SUDAAN software, followed by cosinor analyses for the variation of month and weekday of injury. Three-dimensional topographic representations for weekday-by-month analyses were also created. Over this 13-year time span, there were more than 21 million injury visits due to assault, accounting for 6.57% of all ED visits. While there was no change in the incidence of total number of assaults over the study period, there was a significant increase in the annual percentage incidence of IPV (1.17%; p = .0094) and robbery (2.56%; p = .0001). Cosinor analyses demonstrated a mid-summer peak for all assault types except for robberies (late summer). All assault types showed a weekend peak (late Saturday or early Sunday). Topographical contours exhibited a peak in July and August on early Sunday for all assaults, however the month varied by the type of assault, with weekend peaks in the spring and winter for IPV. This information can be used in prospective resource planning for management and prevention strategies.